PENGARUH PENYULUHAN MENGGUNAKAN MEDIA KOMBINASI PHANTOM DAN FLASH CARD TERHADAP PENGETAHUAN MENYIKAT GIGI PADA ANAK DI TK AISYIYAH 32 BANJARMASIN - jannah, fathul; astu rahman, waljuni; isnawati, isnawati (JURNAL TERAPIS GIGI DAN MULUT, 2022)
Knowledge of dental and oral health in school children needs special attention becausethey are undergoing a process of growth and development. The condition of the previous teeth willaffect the development of dental health in adulthood, therefore it is necessary to take dental andoral health education from an early age. This study aims to determine the effect of counseling usinga combination of phantom and flash card media on tooth brushing knowledge in children atAisyiyah 32 Kindergarten Banjarmasin. This type of research is a quasi-experimental (quasi-experimental). Analyzed using Paired Sample T-Test. The sample of this study was Aisyiyah 32Kindergarten children who were willing to be respondents, the sampling technique used waspurposive sampling technique. The results of the study on the effect of counseling on brushingteeth before 7,16 and after 9,64. The results Paired Sample Test obtained a mean different value(difference in average) of 2.48, with the known t-count value of 2.909, the p value of the test showsp = 0.000, so it is smaller than 0.05, (p = 0.000 < 0.05).The conclusion of this study is that there isan effect of counseling using phantom and flash card combination media on knowledge of brushingteeth in children at Aisyiyah 32 Kindergarten Banjarmasin which shows that counseling withPhantom and Flash Card Combination Media is effective in increasing students' knowledge abouthow to brush their teeth.